Socio-Economic Determinants of School Dropouts: An Evidence from Households in Pakistan - Satti, Rizwan Ahmed; Jamil, Muhammad (iRASD Journal of Economics, 2021)
The present study analyzed the determinants of children who dropped out from school in Pakistan, based on PSLM microdata. The study employed the advanced econometric technique “the logistic regression model “to identify the correlates of the problem; thereby analyzing the marginal effects of the multiple attributes. The analyses show that a female child is more likely to dropout from school as compared to a male child. The education of the household head is also a significant contributor to reducing dropouts. Mother education also reduces the chances of a child to dropout from school. An employed mother will increase the chance of a child to dropout from school as compared with the unemployed mother. Other factors which reduce the chances of child dropouts from school are the female household head, lower distance from middle and secondary school, household wealth, and per capita household income. If household head belongs to agriculture sector then there are more chances that their child dropped out from school. Household economic condition is also a very important factor in reducing dropouts. If the economic condition of a household is better off than before then there is less chance of the child to dropout from school. Similarly, the economic situation of the community where the household resides also affects dropouts. If the community’s economic situation is better than before then it reduces the chance of child dropout.